The Local Wisdom Existence of Swidden Agriculture on Wawonii Island - Sitti Rosmalah; Ahmad Muhlis Nuryadi; Samsul Alam Fyka (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2022)
The study assessed the existence of the local wisdom of swidden agriculture on Wawonii Island. Specifically, it identified the farming patterns in Wawonii Island and analyzed the local wisdom of swidden agriculture in Wawonii Island. Purposive sampling procedures were used to get an informant sample, and proportionate random sampling was used to get a farmers' sample. Informants in this study came from community leaders, village staff, and the agriculture and forestry service district. Konawe Islands and extension workers, while the sample of farmers totalling 30 people was taken proportionally from each sub-district on Wawonii Island. Data were collected using a structured interview schedule and summarized with percentages and means. The analytical method used is descriptive qualitative analysis. Results showed the local wisdom of the farmers who used to be slowly fading away. Farmers no longer carry out the tradition of land clearing as before due to limited land. The addition of chemical inputs also slowly began to be carried out because of the short period of resting land. The people of Wawonii Island manage their fields using two agricultural patterns carried out for generations: mixed cropping and monoculture. The existence of local wisdom of field farmers has decreased. The study recommended that the government provides policies that support the preservation of the local wisdom of the people that contribute positively to the balance of forest and land resources therein.